Effects of resistance exercises on rotator cuff muscle mechanical characteristics in shoulders with and without rotator cuff tears - Andrew J. Nasr; Henry Wang; Jijia Wang; Michael Khazzam; Nitin B. Jain; Yen-Sheng Lin (PLoS ONE, 2026)
Background Rotator cuff tears are the primary cause of shoulder pain, often managed with resistive exercise. Understanding how rotator cuff muscles respond to low-intensity rehabilitation-based exercise is critical for optimizing rehabilitation strategies, yet these responses remain poorly characterized. Methods This study investigated changes in shear wave speed, cross-sectional area, and strength of the supraspinatus and infraspinatus muscles following a 30-repetition isometric contraction protocol at 20% of isometric volitional contraction in shoulders with and without rotator cuff tears. Three-way mixed ANOVAs with repeated measures were performed to evaluate the main effects of tear status, baseline vs post-exercise, passive and active conditions on supraspinatus and infraspinatus as well as the interaction between main effect and cross-sectional area and shear wave speed. Results Twenty participants were assessed using ultrasound imaging pre- and post-exercise. The findings revealed that participants with rotator cuff tears experienced a significant reduction in passive supraspinatus shear wave speed ( p = 0.0021), indicative of increased muscle compliance, while asymptomatic participants exhibited no significant change. Cross-sectional area increased significantly post-exercise in both groups under active conditions (asymptomatic group: p = 0.0046 and symptomatic group: p = 0.0020), though no change was observed in rotator cuff tear participants during passive testing ( p = 0.8900). Strength assessments showed marked declines in both groups following exercise ( p -values <0.005), reflecting peripheral weakness. Conclusion These findings suggest that rotator cuff tears are associated with maladaptive reductions in supraspinatus muscle stiffness during acute exercise, potentially impairing functional capacity and necessitating longer recovery periods. In contrast, asymptomatic participants maintain supraspinatus stiffness despite weakness, underscoring differential adaptation to low-intensity exercise.